Pelatihan Pembekalan Prakerin Siswa Jurusan Rekayasa Perangkat Lunak Pada SMK UISU Siantar - Surya Darma; Fahmi Firzada; Wendi Robiansyah; Rizky Khairunnisa Sormin; Dedy Hartama (Fakultas Teknik Universitas Cenderawasih, 2023)
UISU Siantar Vocational School is one of the private vocational schools and is one of the best Vocational Schools in Siantar. All SMK students are required to take part in industrial/prakerin work practices. The problem faced by partners is that when industrial work practices students do not have knowledge about the world of work and work ethic. A provision is needed for SMK students before industrial work practices take place. The training is carried out by providing material on an overview of the current labor market situation and the prospects for various types of jobs in the future. This activity is carried out by discussing between the training participants and the speakers. After training, the next stage in this activity is mentoring or teacher guidance. In the mentoring activities the training students are taught practice in behaving during the apprenticeship. The purpose of this activity is that students can get maximum work experience while carrying out an internship. Not only that, it is hoped that this internship activity can be used by students to demonstrate their abilities or capabilities in the world of work so that many people believe in and are interested in their abilities.